Clozapine for treatment resistance in early psychosis: a survey of UK clinicians' training, knowledge and confidence - Ebenezer Oloyede; Bethany Mantell; Julie Williams; Serena Lai; Sameer Jauhar; David Taylor; James H. MacCabe; Robert Harland; Philip McGuire; Graham Blackman (SAGE Publishing, 2022)
Background: Clozapine is the only medication licenced for patients with psychosis that is resistant to conventional antipsychotic treatment. However, despite its effectiveness, it remains widely underutilised. One contributory factor for this may be clinicians' lack of confidence around the management of clozapine. Objective: We conducted a survey of clinicians working in Early Intervention in Psychosis (EIP) services to determine their training needs for clozapine management in EIP services. Methods: An electronic survey was made available to all clinicians working in EIP services in England. The survey assessed confidence and training needs regarding managing clozapine in patients with treatment-resistant psychosis. Quantitative data were analysed using total mean scores and the Mann-Whitney U test. Results: In all, 192 (27%) of approximately 700 clinicians from 35 EIP services completed the survey. Approximately half (54%) had not received training on treatment with clozapine. Experience of training was higher in prescribers than non-prescribers, and among medical than non-medical clinicians. Previous training was associated with significantly higher confidence in offering clozapine and managing treatment-resistant psychosis ( p  < 0.001). Confidence levels with managing treatment-resistant psychosis and clozapine were relatively high (mean = 4 out of 5, SD = 1). Respondents were most confident about monitoring mental health response to treatment (mean = 5, SD = 1). Participants were least confident about how to discontinue clozapine treatment safely (mean = 3, SD = 1). Conclusion: Most clinicians working in EIP have not received training on the use of clozapine. This may account, in part, for the underutilisation of clozapine in EIP services. The provision of training in the identification of treatment-resistant psychosis and the use of clozapine will likely improve the detection and management of treatment resistance in the early phase of psychosis.